Digital Marketing Adoption Strategy of Legendary Micro, Small, and Medium Enterprises (MSMEs) in Makassar City - Sahid, Abdul; Hazan, Hazan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This study explores the adoption of digital marketing strategies among Micro, Small, and Medium Enterprises (MSMEs) in Makassar, Indonesia, focusing on their phased approach, responses to market pressures, and the role of organizational readiness in digital transformation. Utilizing a qualitative case study design, in-depth interviews and observations were conducted with five well-established culinary MSMEs. Thematic analysis and manual coding were used to identify key themes and validate findings on their digital marketing adoption journey. The findings reveal a staged adoption process, beginning with basic social media use and evolving toward e-commerce platforms, targeted advertising, and customer relationship management (CRM) systems. Market pressures—such as heightened competition and shifting consumer preferences—were key drivers, though adoption levels varied. For instance, while 80% of respondents had adopted e-commerce platforms, others remained limited to social media engagement due to lower organizational readiness. Organizational readiness, encompassing technology infrastructure, financial capacity, and leadership attitudes, was crucial for effective digital adoption. The study highlights the need for tailored support, including digital literacy training, financial assistance, and an innovation-friendly culture, to enhance MSME competitiveness in the digital economy. This research contributes to the broader discourse on digital marketing adoption by providing strategic recommendations to support MSME growth in a digital landscape.